State emergency plans: assessing the inclusiveness of vulnerable populations. (8th March 2010) - Bennett, DeeDee
The US federal government's involvement in emergency management has evolved in magnitude since the 1800s. Each significant change usually occurred following a catastrophic event. The USA had two large-scale emergencies in 2001 and 2005 – man-made (September 11 terrorist attacks in 2001) and natural (Hurricane Katrina in 2005) – that shaped a new policy regarding emergency management. These disasters revealed numerous failures in planning for, preparedness for and response to disasters. Of the identified failures, accessible emergency communications for all and, distinctively, for Vulnerable Populations (VPs), were studied in this paper. With over 37 million people over 65 years of age and 38.22 million people (over the age of 5) with disabilities, it is important that these populations be appropriately included in emergency management plans. This paper looks at the change in national emergency policy from the National Response Plan to the National Response Framework in 2008 to determine how this change has affected the state emergency plans. The results show that recent changes in the national emergency plan has had little effect on state emergency plans (in Federal Emergency Management Agency (FEMA) Region IV) with regard to VPs.